Working equids presented at a veterinary reference center in southern Chile (2015-2021) - Duran, Maria C.; Deride, Camila B.; Uberti, Benjamin (Austral Journal of Veterinary Sciences, 2023)
In Chile many families still rely on working equids as a fundamental source of income. Their use is particularly important for harnessing and transport of people and goods, in agriculture as well as in the leisure industry. Information on common emergency and clinical conditions in working equids is important to identify foci for owner education and to guide action towards disease prevention and animal welfare. The aim of the report was to highlight details about the clinical presentation of working equids at a veterinary reference center in southern Chile. Hospital records from working equids presented pro bono from 2015 to 2021 at the Equine Clinic of the Veterinary Teaching Hospital of the Universidad Austral de Chile were evaluated and included. A total of 107 working equid cases were recorded. The age range went from 1 day of age to 19 years (8.2±5.19 years). Most cases were not hospitalized and discharged on the same day of presentation (n=52). Horses were presented for evaluation of reproductive status (23%), lameness (15%) and castration (13%). Common reproductive diagnoses were uncomplicated castration (13%), barren (9%) and pregnant (8%) mares. Causes of lameness included laceration and wounds (40%), distal limb fractures (15%) and foot abscesses and/or poor foot care (10%). Only 4 cases of colic (3.7%) were presented over the years. Transrectal ultrasonography was the most used imaging tool, followed by radiography and endoscopy. Laboratory analysis was only performed in 15% of all cases. This is the first report on clinical presentation of working equids at a veterinary care reference center in southern Chile. Most working equids seek veterinary care to aid reproduction and treat conditions related to their use. Findings suggest that animal use, husbandry and welfare can be improved.